Industrial Applications of Limestone Deposits of Kohat, NWFP: A Research Towards the Sustainability of the Deposits (Biological Sciences - PJSIR, 2007)
Ch emica l  an a l yses,  petrograph ic studies and  ph ysical  tests of l i mestone deposi ts  i n  the v ici n i t y of Kohat along Ban n u Road , H an gu  Road and Rawal pi ndi Road were carried out to categorize th ese reserves,  l ocal i ty-wise, for thei r specified  i ndu strial  u ses. Limestone of Kohat area was found to be genera ll y good for construction purposes. Theeposi t s on the Han gu Road were of good q ual ity with more th an 97% CaC0  and sui table for u se i n chemical, i ron and3steel i nd ustrie s, for glass maki n g, soda ash man ufacture etc. The deposi t of Bann u Road w ith 96.5% CaC0 can be3u sed for sugar refin i n g, pai nt i nd u stry, fl ue gas desulph u ri zat i on, an i mal feed etc. The l i m estone deposit of Rawa l pi n d iRoad  i s i nferior  i n  q ual i t y h avi n g 95.2 % CaC0 .  It can  be  ut i l i zed  i n  ru bber  i nd u stry, as ceramic w h i ti n g, bui ldi n g3materi als, rock wool etc.